Discovery of pulsational line profile variations in the Delta Scuti star HD21190 and in the Ap Sr star HD218994 - Gonzalez, Jorge Federico (2008)
Asteroseismology has the potential to provide new insights into the physics of stellar interiors. We have obtained Ultraviolet and Visual Echelle Spectrograph high time-resolution observations of the δ Scuti star HD21190 and of the Ap Sr star HD218994 to search for pulsational line profile variations. We report the discovery of a new roAp star, HD218994, with a pulsation period of 14.2min. This is one of the most evolved roAp stars. No rapid pulsations have been found in the spectra of the cool Ap star - δ Scuti star HD21190. However, we detect with unprecedented clarity for a δScuti star moving peaks in the cores of spectral lines that indicate the presence of high-degree non-radial pulsations in this star.